2010
DOI: 10.1007/s10616-010-9289-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient production of recombinant IgG by metabolic control and co-expression with GLUT5 in a fructose-based medium

Abstract: A fructose-based cell culture is suitable for the process control of protein production because of slow sugar consumption rate and low lactate accumulation. The fructose transporter, GLUT5, mediates its incorporation into cells and is required for the fructosebased culture. In order to produce efficiently recombinant IgG by metabolic control and co-expression with GLUT5 in a fructose-based medium, an IgG and GLUT5 co-expression vector was constructed and transfected into the human myeloma derived cell line, SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…The gene targets for cell modification are usually selected based on their known biological functions and the desired phenotypic outcome. For example, proapoptotic and antiapoptotic genes have been manipulated to extend the longevity of cultured cells (Baek et al, 2017; Cost et al, 2010); and genes involved in sugar transport have been manipulated to improve the metabolic efficiency of the producing cells (Inoue et al, 2010; Paredes et al, 1999). However, this approach is limited to genes with known function, whose altered expression may achieve the desired phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The gene targets for cell modification are usually selected based on their known biological functions and the desired phenotypic outcome. For example, proapoptotic and antiapoptotic genes have been manipulated to extend the longevity of cultured cells (Baek et al, 2017; Cost et al, 2010); and genes involved in sugar transport have been manipulated to improve the metabolic efficiency of the producing cells (Inoue et al, 2010; Paredes et al, 1999). However, this approach is limited to genes with known function, whose altered expression may achieve the desired phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…These engineered cells were characterized by a better use of the main carbon source, consuming a lower amount of carbon molecules and producing less lactate. To further investigate the impact of SLC2A5 gene overexpression, in 2010 Inoue and collaborators reported that cells derived from human myeloma overexpressing GLUT5 were able to achieve more than 1.5 times the cell density reached by wild-type cells and produce more than 2 times the amount of recombinant protein [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ning et al 2012). The expression of recombinant proteins under the control of a cell-specific promoter allows the characterization of their role in a cell-specific manner (Montana et al 2011;Cai et al 2010), or the production of promising therapeutic proteins such as immunoglobulins (Inoue et al 2010). Although the potential of transfection is enormous, transfection of many primary cells present many technical challenges.…”
Section: Introductionmentioning
confidence: 99%